Manager-Employee Relationships during Turbulent Times at a Gold Mine in South Africa - Schultz, Cecile; KüselReulene (Journal of Economics and Behavioral Studies, 2019)
This article aims to provide new conceptual insights into the responsibilities of an engineer who acts as a plant manager and who has to deal with employee relations during a turbulent time at a gold mining plant in South Africa. A qualitative research approach was used to gather the data in this study. Trustworthiness of the research was ensured by applying various reasoning strategies, such as content analysis, inductive reasoning, blending, bracketing and understanding in order to interpret the data. The first group interview comprised managers as well as engineers who were appointed as managers, the second, administrative employees from the service departments, and the third, artisans and foremen employed at the mine. Qualitative content analysis was used to analyse the transcripts. The recurring themes from the group interviews were ‘employee empowerment’, ‘trust building’, ‘employee voice’ and ‘development of skills’. A conceptual framework for manager-employee relations during troubled times was developed from the findings. The essential responsibilities of a gold mining plant manager during periods of turbulence were described.